2014
DOI: 10.1007/s00438-014-0961-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and expression analysis of a MADS-box gene superfamily involved in ovule development of seeded and seedless grapevines

Abstract: MADS-box transcription factors are involved in many aspects of plant growth and development, such as floral organ determination, fruit ripening, and embryonic development. Yet not much is known about grape (Vitis vinifera) MADS-box genes in a relatively comprehensive genomic and functional way during ovule development. Accordingly, we identified 54 grape MADS-box genes, aiming to enhance our understanding of grape MADS-box genes from both evolutionary and functional perspectives. Synteny analysis indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 82 publications
8
51
2
Order By: Relevance
“…All the selected DEGs included genes involved in flower and seed identity like VvMADS39 , VvMADS45 , VvSTM and AP2 , genes related to seed coat development like VvNAC26 , VvNAC86 , SCD1 and SCD2 ,genes related to endosperm development and epigenetic regulation like VvPHE1 , VvDME and VvDDM1 , and genes associated with hormone balance like GRAS , GH3-1 and GH3-9 . Besides, the expression patterns of two MADS-box genes VvMADS45 (GSVIVT01009393001) and VvMADS39 (GSVIVT01008139001) were found to be consistent with those presented in a previously published study [34]. Moreover, based on the above mentioned results, 15 out of the 30 DEGs were further selected and subjected to qRT-PCR validation using samples ‘V-Seeded’ (seed mixtures from another 4 seeded progeny) and ‘V-Seedless’ (seed mixtures from another 4 seedless progeny) (Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…All the selected DEGs included genes involved in flower and seed identity like VvMADS39 , VvMADS45 , VvSTM and AP2 , genes related to seed coat development like VvNAC26 , VvNAC86 , SCD1 and SCD2 ,genes related to endosperm development and epigenetic regulation like VvPHE1 , VvDME and VvDDM1 , and genes associated with hormone balance like GRAS , GH3-1 and GH3-9 . Besides, the expression patterns of two MADS-box genes VvMADS45 (GSVIVT01009393001) and VvMADS39 (GSVIVT01008139001) were found to be consistent with those presented in a previously published study [34]. Moreover, based on the above mentioned results, 15 out of the 30 DEGs were further selected and subjected to qRT-PCR validation using samples ‘V-Seeded’ (seed mixtures from another 4 seeded progeny) and ‘V-Seedless’ (seed mixtures from another 4 seedless progeny) (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, NAM ( NO APICAL MERISTEM ), CUC1 ( CUP-SHAPED COTYLEDON ) and CUC2 , all NAC genes, have been reported to be involved in regulating secondary cell wall biosynthesis [39, 40]. Many reports have indicated that MADS-box genes play critical roles in ovule, seed and flower development [34, 41, 42] and the expression of VvMADS28 , VvMADS39 and VvMADS45 in this current study was consistent with previous analysis of seeds from multiple seeded and seedless grape cultivars [34]. Additionally, TFs such a GRAS and HB are involved in GA and ABA signal transduction, and TRs such as AUX/IAA are important in auxin regulation [43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the grape berry-specific basic helix-loop-helix transcription factor VvCEB1 was reported to affect cell size [14]. In addition, some MADS-box genes, which show strong homology to an Arabidopsis ovule identity gene, were found to be differentially expressed during ovule development in multiple seeded and seedless grape cultivars, indicating a potential role in ovule development [15]. Moreover, nowdays omics analysis has cast light on mechanism related to grape seedlessness, evidence showed that parthenocarpy in the grapevine seedless somatic variant Corintobianco was caused by the absence of a mature macrogametophyte which was probably due to meiosis arrest [16].…”
Section: Introductionmentioning
confidence: 99%